2017
DOI: 10.1139/cjpp-2016-0269
|View full text |Cite
|
Sign up to set email alerts
|

Trigonelline attenuates hepatic complications and molecular alterations in high-fat high-fructose diet-induced insulin resistance in rats

Abstract: The present study aimed to evaluate the effect of trigonelline (TRG) on the hepatic complications associated with high-fat high-fructose (HFHF) diet-induced insulin resistance (IR) in rats. IR was induced by giving a saturated fat diet and 10% fructose in drinking water to rats for 8 weeks. Insulin-resistant rats were orally treated with TRG (50 and 100 mg/kg), sitagliptin (SIT; 5 mg/kg), or a combination of TRG (50 mg/kg) and SIT (5 mg/kg) for 14 days. Liver homogenates were used for assessment of hepatic lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…In accordance with previous studies (Afifi et al, 2016, Lozano et al, 2016, the present study confirms the relationship between HFHF diet-induced IR model in rats and its impact on hepatic tissue such as hepatic steatosis complicated by fibrosis, inflammation, and oxidative stress.…”
Section: Discussionsupporting
confidence: 80%
“…In accordance with previous studies (Afifi et al, 2016, Lozano et al, 2016, the present study confirms the relationship between HFHF diet-induced IR model in rats and its impact on hepatic tissue such as hepatic steatosis complicated by fibrosis, inflammation, and oxidative stress.…”
Section: Discussionsupporting
confidence: 80%
“…The signs and symptoms of metabolic syndrome may be induced in rats by feeding them diet rich in carbohydrates and fat 10 . The multifactorial disease NAFLD has many complex pathophysiologies, among which insulin resistance (IR), obesity and dyslipidemia are well known clinical markers 8,11 . Hepatic fat accumulation results from the synergistic effects of oxidative stress, hepatic lipid dysregulation and pro-inflammatory cytokines.…”
Section: Introductionmentioning
confidence: 99%
“…[ 59 ] The present data showed increased MDA associated with decreased SOD and CAT activities in insulin‐resistant diabetic rats; these results are in line with those of previous studies that reported that lipid peroxidation significantly increased during hyperglycemia. [ 60,61 ] Under hyperglycemic conditions, SOD may undergo glycation at specific lysine residues. [ 62 ] In addition, CAT is susceptible to free radical attack, [ 63 ] thus inactivating them.…”
Section: Discussionmentioning
confidence: 99%